Morbimortalidade por diabetes mellitus no município de São Paulo, 2003 a 2018 - Argachoff, Glaucia Greice Martins (2020)
As a result of population aging and the epidemiological transition, there is a high prevalence of Diabetes Mellitus in the Brazilian population. Estimates indicate that in 2030 about 12.6% of Brazilians will be diabetic, exceeding the projections of global prevalence that correspond to 7.7%. There are also high mortality rates resulting from this disease. Given the magnitude of DM, its clinical, social and health system impacts, monitoring hospitalization and death rates represents an important strategy for assessing the management and effectiveness of strategic policies and programs aimed at meeting this demand. The applied methodology has a retrospective analytical ecological character, with quantitative sociodemographic analyzes of secondary data on morbidity and mortality in the city of São Paulo. The data were obtained through Hospital Information Systems and on Mortality. The aim of the study was to analyze the impact of Fededral Law 11.347 of 2006 on morbidity and mortality from diabetes mellitus in the city of São Paulo in the period between 2003 and 2018, considering the rates and proportional distribution according to sociodemographic variables.The results of the study showed reductions in the rates of hospitalizations and general deaths, specific for both gender, and in the age groups above 30 years of age. There was an increase in the proportion of lethality among men and the elderly over 70 years. Regarding color race, there was an increase in the proportion of hospitalizations between blacks and browns, and those with less education. The comparison of the averages of the periods before and after the implementation of the Law showed significance in relation to the decline of the observed averages, in the rates of hospitalizations in the female gender; and in age groups aged 50 years or more, and deaths in the general sample; male, and in the age group between 30 and 69 years old. It was concluded that the analysis of the observed results contributes to the strategic surveillance of the mortality and hospitalization indicators in the population of the city of São Paulo, serving as a tool in the process of continuous evaluation of the implemented public programs and policies, as well as promoting decision making, by health managers, regarding the planning and necessary adjustments to services and actions for the studied sample.